COMPOSIÇÃO E DISTRIBUIÇÃO VERTICAL DE FORMIGAS (HYMENOPTERA:FORMICIDAE) NO PARQUE NACIONAL DA CHAPADA DAS MESAS, MARANHÃO - BRASIL - MENEZES, Henrique Morais (2024)
The Cerrado hosts ants that play an essential role in biodiversity. In this ecosystem, the microclimate presents a heterogeneous distribution, both horizontally and vertically. Considering the vertical profile, the resources available in a forest vary across strata, such as the canopy, sub-canopy, and layers above and below the soil. Fires alter ant populations, influencing the soil and arboreal strata and affecting available resources either positively or negatively for ant communities. This study aimed to evaluate variables associated with the occurrence, frequency, and distribution of ant species, with the collection site being the Chapada das Mesas Nacional Parque (PNCM) in the state of Maranhão. The collection areas were chosen based on satellite images (LANDSAT 8/9), marking 26 units with three sample sub-points each, where traps were installed on the ground and in trees, totaling 156 traps. The results revealed 124 species and morphospecies of ants, highlighting Myrmicinae, Formicinae, and Ponerinae. Additionally, the first record of the genus Myrmicocrypta for the state of Maranhão was documented, as well as Prionopelta antillata in pitfall traps. The research revealed a remarkable biodiversity of ants, standing out compared to other studies conducted in the Cerrado, and this was achieved using only one collection method. The analyses indicated that variables such as litter, tree density, NDVI, and spatial distance play important roles in determining patterns in the studied ecosystem. The composite model, considering these variables, highlights the complexity of environmental interactions. These findings have significant implications for future research and management practices, contributing to a deeper understanding of the factors that influence the dynamics of this environment.